Letter from Ludwig Bendix to Max Bredig, March 12, 11941 - Bendix, Ludwig (1941)
Ludwig Bendix, New York investment banker, informs Max Bredig (1902-1977) that a letter sent to Viktor Homburger's (1888-1968) German address was returned. Bendix is a longtime friend and colleague of Homburger, who is Bredig's brother-in-law. Bendix is assisting Bredig in securing immigration visas for Viktor and his wife, Max's sister, Marianne Homburger (1903-1986).
Keywords: Bredig, Max Albert, 1902-1977; Bendix, Ludwig, 1877-1954; Emigration and immigration; Homburger, Viktor, 1888-1968; Homburger, Marianne, 1903-1986